Pola Kejadian Upwelling dalam Fishing Map and Calender (FISMAC) di Laut Banda - Lestari, Rizka Erwin (Buletin GAW Bariri (BGB), 2024)
The Banda Sea is one of the fertile waters and has the potential for fisheries and is the largest fishing area in Indonesia. Apart from that, the Banda Sea has very complex seabed topography and is crossed by the Indonesian Cross Current (Arlindo) route from the Pacific Ocean, which adds to the complexity of conditions in the Banda Sea, thereby increasing the potential for upwelling in this region. The aim of this research is to determine the characteristics of upwelling event patterns in the Banda Sea for Fishing Map and Calender (FISMAC) mapping. The data used in this research includes surface wind data, sea surface temperature and chlorophyll – a data for 2009 – 2019. Based on the analysis, this research shows that the upwelling phenomenon in the Banda Sea occurs from June to October where sea surface temperatures experience a decrease and when the easterly wind strengthens (high wind speed). The formation of cyclonic wind patterns has no effect on upwelling events. The upwelling process in the Banda Sea occurs on the southern coast, namely Buru Island, Ambon and Seram. Apart from that, the upwelling phenomenon causes an abundant distribution of chlorophyll – a from June to September. This could be a trigger for the distribution of fish in the area. The upwelling phenomenon reaches its peak in August. In the Fishing Map and Calendar (FISMAC) mapping, it can be seen that there is an increase in potential fishing zones in the Banda Sea from June to October.